Patient Transitions Relevant to Individuals Requiring Ongoing Ventilatory Assistance: A Delphi Study - Louise Rose; Robert A Fowler; Roger Goldstein; Sherri Katz; David Leasa; Cheryl Pedersen; Douglas McKim; the CANuVENT Group (Canadian Respiratory Journal)
BACKGROUND: Various terms, including ‘prolonged mechanical ventilation’ (PMV) and ‘long-term mechanical ventilation’ (LTMV), are used interchangeably to distinguish patient cohorts requiring ventilation, making comparisons and timing of clinical decision making problematic.